Importance of the corpus luteum at the beginning of the protocols to syncronize estrus in sheep - Campero-Cruz, Angel; Sánchez Torres Esqueda, María Teresa; Figueroa-Velasco, José Luis; Martínez-Aispuro, José Alfredo; Nieto-Aquino, Rafael; Cordero-Mora, José Luis; López-García, Susana; Martínez-Cruz, Israel; Cárdenas-León, Mario (Ecosistemas y Recursos Agropecuarios, 2023)
The aim was to examine the exogenous supply of progesterone, and the influence of the corpus luteum (CL) at the beginning of the estrus synchronization protocols in sheep, for 6 and 11 days, on reproductive variables. The sheep were presynchronized to obtain a premature or functional CL at the beginning of the synchronization period to be evaluated. Estrus presentation was lower in short treatments; This triggered a difference (p < 0.05) in pregnancy rate between short and conventional treatments. On the day of estrus, steroid concentration was different: progesterone was higher in short treatments; while estradiol was lower in the short treatment with CL. The presence of a premature or functional CL at the initiation of the treatments commonly used to synchronize estrus does not modify the expression of the reproductive variables; Nevertheless, in short treatments the expression is affected. It is important to use ultrasonography to corroborate what happened at the ovarian level.